Travessia periférica: a trajetória do pintor Waldemar Belisário: um estudo sobre a desconstrução do cenário artístico paulista - Marcondes, Ana Maria Barbosa de Faria (2006)
Hegemonic relations characterized the arts in the city of Sao Paulo in the beginning of twenty century. At this time, the modernistas were the center of everybody s attention which obfuscated the work of other artists in the city. It was not the case of painter Waldemar Belisário Pellizzari. Stigmatized as an Italian-immigrant blooded painter, Pellizzari was an outsider. His works not only revealed considerable points of tangency in the social circle of paulista aristocracy but also brought him close to Tarsila do Amaral and other artists of his time. In spite of that besides of becoming the godson of Lídia and José Estanislau do Amaral, the parents of Tarsila , Pellizzari remained in the condition of a henchman. In order to rebuild the trajectory of Waldemar Belisário Pellizzari,. this dissertation is divided in four chapters. The first one studies the construction of sociability made by the triangle Tarsiwald Pagu Belisário. Such construction demanded a cutting in the formation of the cultural/social capital as elements of demarcation of the frontiers of sociability (which is the name of the chapter). The Space in the Arts chapter II explores the difficulties faced by the painter and his friends to realize the Primeira Exposição Geral de Belas Artes , which would be his chance of becoming part of the Paulista artistic circuit. The conflict among the expositions of 1922 stresses out the geographic spaces filled by the two groups. Chapter III stresses out Pellizzari s opposition to the marchands and his struggle through his Travessias toward the freedom of the artist/artesian. Chapter IV explores the touch of the painter in the construction of the artistic scenario, pointing out the expositions in which he participated and the building of social nets (also known here as triangles of sociability ). We reconstruct both Pellizzari s artistic trajectory and biography by examining the formation and evolution of artistic environment in Sao Paulo (1922, 1951 and 1975). For doing so, we use both the historical and the sociological method of investigation. The first is to examine printed (newspapers, magazines and catalogs) and personal documents (letters, objects, photos, clippings, postal cards and official documents), and, the latter, to systematize interviews, rebuild trajectories and nets of power relations